Tumour necrosis factor (TNF-alpha) and neurological disorders in HIV infection. Issue 3 (March 1992) - Mastroianni, C M; Paoletti, F; Valenti, C; Vullo, V; Jirillo, E; Delia, S
Abstract : Tumour necrosis factor (TNF-alpha) concentrations were determined in the CSF from 42 HIV-infected patients, with or without CNS involvement. In addition, 14 subjects with various neurological disorders but without HIV antibodies were included as controls. Raised CSF concentrations of TNF-alpha (greater than 40 ng/l) were detected both in patients with AIDS dementia complex (ADC) (6/9) and with CNS opportunistic infections (10/19) and, less commonly, in HIV infected subjects without CNS diseases (2/14) and in anti-HIV negative controls (1/14). The highest CSF concentrations of TNF-alpha (greater than 100 ng/l), however, were found in seven out of eight patients with cryptococcal meningitis. Although a role for TNF-alpha in demyelinating lesions associated with ADC has been suggested, our results indicate that a clear elevation of TNF-alpha in the CSF from HIV positive patients mostly occurs in acute inflammatory disorders, such as cryptococcal meningitis.